THE IMPACT OF READING STRATEGIES ON ENGLISH LANGUAGE PROFICIENCY - Behruzkhon Yuldoshev Behzod ugli (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
This article explores the importance of using effective reading strategies in improving English language proficiency among EFL learners. The research highlights the relationship between reading comprehension techniques and overall language development, focusing on cognitive, metacognitive, and social-affective strategies that enhance vocabulary, grammar, and critical thinking skills.